2020
DOI: 10.1007/s40820-020-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Surface-Functionalized Cellulosic Nanostructures as Biocompatible Antibacterial Materials

Abstract: HIGHLIGHTS • The most common chemical treatments of cellulose to synthesize nanostructured cellulose are highlighted. • Various surface modifications of cellulose to develop non-leaching and durable antibacterial materials are discussed. • Biocompatibility and antibacterial performance of non-leaching surface-modified cellulosic materials along with their current challenges are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(157 citation statements)
references
References 179 publications
(222 reference statements)
2
155
0
Order By: Relevance
“…Cationic nanocellulose compounds have an intrinsic antibacterial property since the cell walls of both Gram-positive (G+) and Gram-negative (GÀ) bacteria have a net negative charge, due to the presence of phosphate groups in the peptidoglycan and phospholipids of the outer membranes of G+ and GÀ bacteria, respectively. 79 Tyagi et al (2019) 82 have demonstrated the combination of CNC with chitosan for tissue coatings for antimicrobial and superabsorbent tissue papers. This modified nanocellulose can inhibit 99% of the growth of Escherichia coli.…”
Section: Nanocellulose As An Antimicrobial Materials For Bacteriamentioning
confidence: 99%
“…Cationic nanocellulose compounds have an intrinsic antibacterial property since the cell walls of both Gram-positive (G+) and Gram-negative (GÀ) bacteria have a net negative charge, due to the presence of phosphate groups in the peptidoglycan and phospholipids of the outer membranes of G+ and GÀ bacteria, respectively. 79 Tyagi et al (2019) 82 have demonstrated the combination of CNC with chitosan for tissue coatings for antimicrobial and superabsorbent tissue papers. This modified nanocellulose can inhibit 99% of the growth of Escherichia coli.…”
Section: Nanocellulose As An Antimicrobial Materials For Bacteriamentioning
confidence: 99%
“…However, it still needs to be better studied in the fungi and viruses, for example. There will be a size of the alkyl group for each different microorganism that will be effective, resulting in varied molecular masses of the QACs used [ 8 ]. According to data from List N of the US Environmental Protection Agency (EPA), of the 430 disinfectants for use against SARS-CoV-2, 216 contain QACs as an active ingredient.…”
Section: Coating Strategies Using Polymeric Matricesmentioning
confidence: 99%
“…Generally, polymeric antimicrobial agents have the following advantages: (1) in general, they do not volatilize and are chemically stable; (2) the intended application temperature is the same as the storage; (3) its insolubility in water allows application in water disinfection processes; (4) the biomaterials do not permeate through the skin; (5) for the most part, their syntheses are easily controlled and economically viable [ 4 , 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this present review, we highlight the current status of nanocellulose-graphene hybrids in multi-sensing applications. As outlined, the basic principles of synthetization, interfacial interactions, Table 1 Tabulation of the synthetization, functionalization, fabrication, and properties for a variety of hybrid NCs-GO/rGO nanocomposite films [166] Copyright © 2020, Springer Nature. b Intra-intermolecular strong hydrogen bonding cellulose structure and glucose monomers alternately rotated degree (180°) with crystalline-non-crystalline regions.…”
Section: Introductionmentioning
confidence: 99%